Digital Talent Transformation: Linking Youth Potential with BUMDes Innovation - Azzuhri, Misbahuddin; Fakhri, Erie Awalil; Huda, Choirul; Afidah, Rosya Putri; Munir, Misbakhul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2026)
This community engagement program aims to address these issues by developing a Digital Talent Pool that integrates youth competencies with the operational needs of BUMDes in Tegalweru Village. Using a Participatory Action Research (PAR) approach, the program involved 30 youth members of Karang Taruna and BUMDes training activities focused on digital profile development, personal branding, and the use of freelance work platforms. The results show that 28 out of 30 participants successfully prepared and validated their curriculum vitae (CV). Additionally, 20 freelance accounts were created, of which 3 participants received actual job offers. The program significantly improved digital literacy, expanded youth employment opportunities, and strengthened digital HR governance at the village level. Therefore, the Digital Talent Pool serves as a strategic model that can be replicated to enhance rural economic resilience and foster BUMDes innovation through local talent empowerment